Criminals’ “talk of crime”. Inmates discourse on crime, fear and dangerousness - Frois, Catarina (Anthropology of Crime and Criminalization, 2020)
In this presentation I discuss data from fieldwork conducted in male prison facilities in Portugal to discuss how individuals define and recognise themselves as ‘criminals’ or even as someone who has ‘committed a crime’. By doing so, my aim is to answer one of this panel challenges, namely “What is conceived as criminal or social harmful?”, through the narratives of those who were labelled by justice as “criminals”, that is, authors of unlawful actions. The discussion revolves on how inmates negotiate the meaning ascribed to themselves, their conduct and the crimes they were convicted of, rejecting the “criminal” label, the depiction of their actions as harmful and, in certain cases, the resulting victims. These narratives are constantly being reformulated within prison environment and amongst peers, constituting another facet of the daily “talk of crime” where reality and fiction emerge according with the interlocutors: judge, correctional treatment staff, other inmates. This means that the perception of their own ‘dangerousness’ also influences how they consider the prison institution, the justness of their conviction, and daily experience within walls. To see themselves as people who committed violent actions, who threatened others or who endangered order, is determinant in their own perception of themselves, in how they rationalise their crime, and negotiate its importance in terms of its impact on society.